Analisis Pengaruh Pemasaran melalui Media Sosial terhadap Loyalitas Merek pada Instagram Tomoo Steak - Rony Adita Muslim; Niken Hendrakusma Wardani; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Nowdays there are many culinary companies with very tight competition. The focus and target of marketing now has changed, which how companier got new customers, and has changed to how company kept customers to be loyal. One strategy that can be used by company using social media. Tomoo Steak is a culinary company that actively engages in customers relationship in anagement throught social media marketing o gain customers loyalty. Customer loyalty is positively influenced when companies doing advantageous campaigns, relevant content, popular contents, various platforms and applications, frequently updated content on social media (Erdogmus & Cicek, 2012). This study tested the relationship between social media marketing and customer loyalty using multiple linear regression analysis. Respondents from this study are followers Tomoo Steak account in Instagram. The data were collected using simple random sampling technique. Result of f test, show independent variables simultaneously or equally influence brand loyalty. The independent variable used in this study contributed 52,2% to the Tomoo Steak brand loyalty. The relevant content variable has the greatest influence brand loyalty. This is because the Tomoo Steak Instagram account presents content that can attract customers to interact with content companies, various platform.